Estimasi Potensi Pembibitan Ternak Kerbau di Kecamatan Ulakan Tapakis Kabupaten Padang Pariaman Provinsi Sumatera Barat, Indonesia (THE ESTIMATION POTENTIAL LIVESTOCK BREEDING OF BUFFALO IN ULAKAN TAPAKIS DISTRICT, PADANG PARIAMAN REGENCY, WEST SUMATRA PR - Putra, Dino Eka; Anwar, Sarbaini; Afriani, Tinda (Jurnal Veteriner, 2018)
This study aimed to determine the potential of buffaloes in Ulakan Tapakis sub-district to produce calves and its viability as a source buffaloes. Casus and questionnaire are used in this study in which three sub-district characterized by high, medium and low buffalo population are chosen quota sampling. The observed variables in this study are the identity of the breeder and the buffalo. The development of buffalo population was analyzed using breeding theory approach. The average increase of the population was analyzed using a time series analysis. The results showed that Net Replacement Rate (NRR) value in male and female of 157.31% and 191.27% and the natural increase (NI) value of 23.66% indicating a moderate increase of the population. This study also shows that the population of buffaloes in the region is sufficient to cover its need. Male and female seed potencial of 4.55% and 5.33% of the population. On average the increase population of buffalo from 2011 to 2015 annual of as much as 172.75 head or 16.53%. Estimated population of buffaloes in 2016 and 2020 as in 1675 head and 2183 head eith average increase population as much as 63 head or 3.40%.
Keywords: Bibit, Kerbau, Potensi, Produktivitas, Ulakan Tapakis